2022
DOI: 10.1155/2022/2099327
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of NPSR1-AS1 as a Novel Diagnostic and Prognostic Biomarker Involved in Immune Infiltrates in Lung Adenocarcinoma

Abstract: The incidence of lung adenocarcinoma (LUAD), the most common subtype of lung cancer, continues to make lung cancer the largest cause of cancer-related deaths worldwide. Long noncoding RNAs (lncRNAs) have been shown to have a significant role in both the onset and progression of lung cancer. In this study, we aimed to investigate the clinical significance and underlying mechanism of lncRNA NPSR1-AS1 (NPSR1-AS1) in LUAD. First, we performed an analysis on TCGA and identified 229 differentially expressed lncRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…So far, some related researchers have also indicated that there are also many limitations in the studies on PCBP1-AS1. In addition, there is a limited amount of highly relevant Hepatocellular carcinoma Proliferation, migration PCBP1-AS1/PRL-3-AKT/PCBP1 Oncogene Up-regulation [20,21] Vulvar squamous cell carcinoma Inhibitor of proliferation, enhance apoptosis PCBP1-AS1/TRAF5/NF-kB Inhibitor Down-regulation [24] Hodgkin lymphoma Proliferation PCBP1-AS1/mRNA Unknown Down-regulation [26] Lung adenocarcinoma Inhibitor of migration PCBP1-AS1/EMT Inhibitor Down-regulation [29][30][31] Cervical cancer Invasion, proliferation, migration PCBP1-AS1/p53/notch Oncogene Up-regulation [34][35][36] Glioma Proliferation, migration and invasion Unknown Oncogene Up-regulation [40] Colorectal cancer Inhibitor, proliferation, tolerance LncRNA-miRNA-mRNA Unknown Up-regulation…”
Section: Methylation Of Lncrna Promoter Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, some related researchers have also indicated that there are also many limitations in the studies on PCBP1-AS1. In addition, there is a limited amount of highly relevant Hepatocellular carcinoma Proliferation, migration PCBP1-AS1/PRL-3-AKT/PCBP1 Oncogene Up-regulation [20,21] Vulvar squamous cell carcinoma Inhibitor of proliferation, enhance apoptosis PCBP1-AS1/TRAF5/NF-kB Inhibitor Down-regulation [24] Hodgkin lymphoma Proliferation PCBP1-AS1/mRNA Unknown Down-regulation [26] Lung adenocarcinoma Inhibitor of migration PCBP1-AS1/EMT Inhibitor Down-regulation [29][30][31] Cervical cancer Invasion, proliferation, migration PCBP1-AS1/p53/notch Oncogene Up-regulation [34][35][36] Glioma Proliferation, migration and invasion Unknown Oncogene Up-regulation [40] Colorectal cancer Inhibitor, proliferation, tolerance LncRNA-miRNA-mRNA Unknown Up-regulation…”
Section: Methylation Of Lncrna Promoter Regionmentioning
confidence: 99%
“…LncRNA has been proved to play an vital role in the occurrence and progression of lung adenocarcinoma. [ 29 ] Li research proved that down-regulation of PCBP1-AS1 significantly enhanced the migration and invasion of cancer cells. [ 30 ] On the contrary, up-regulation of PCBP1-AS1 could inhibit the metastasis of cancer cellula.…”
Section: Performance Of Lncrna Pcbp1-as1 In Different Cancermentioning
confidence: 99%